PERBEDAAN KEJADIAN KONJUNGTIVITIS FOTOELEKTRIK DENGAN METODE PENGELASAN BUSUR DAN PENGELASAN FRICTION STIR WELDING (FSW) - Retno Kamilia Mutiara; Baju Widjasena; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Photoconjuctivitis was an inflammation of conjunctiva caused by welding processes in manufacturing which has ultraviolet radiation. The welder who had experienced with arc welding will have photoconjuctivitis after 4-6 hours in welding process because it has ultraviolet radiation. Appropriate treatment for those welder is that they should have at least 2 days off from welding process. Friction Stir Welding (FSW) was a green welding with no fumes, no flares, and no ultraviolet radiation. But, there was no any study before which described the effects on human caused by FSW. This study aimed to analyze the differentiation of photoconjunctivitis by arc welding and friction stir welding. The study was quasi-experimental study with non randomized pretest-postest control group design. The subjects of this study amounted to 16 as sampels. The result showed that the photoelectrical conjunctivitis has increased 31,25%, Mann-Whitney test showed that there was no difference of photoconjunctivitis by pre welding for those group (p=1,000), Wilcoxon test showed that there was no difference of photoconjunctivitis by pre-post welding in FSW group (p=1,000), Wilcoxon test showed that there was a differentiation of photoconjunctivitis by pre-post welding in arc welding group (p=0,025) and with Mann-Whitney test showed that there was a difference of photoconjunctivitis by post welding for those group (p=0,015). FSW might be considered that it is better for welding process because it has no fumes, no flares, and no ultraviolet radiation, but in fact, that method was not officially perfect, because that method still has fumes, metal flakes, and the probe might be apart in process.